2018
DOI: 10.1371/journal.pone.0193353
|View full text |Cite|
|
Sign up to set email alerts
|

Prescribing patterns and associated factors of antibiotic prescription in primary health care facilities of Kumbo East and Kumbo West Health Districts, North West Cameroon

Abstract: BackgroundInappropriate use of antibiotics is a global public health challenge and has been associated with antibiotic resistance. WHO reports show that efforts to promote rational antibiotic use in developing countries are poor. With the growing number of infections with antibiotic resistant bacteria, rational drug use becomes imperative and studies that promote rational drug use are highly necessary. Considering this, we investigated prescribing patterns and predictors of antibiotic prescription in primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
111
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 53 publications
20
111
4
2
Order By: Relevance
“…This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37]. These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use.…”
Section: Discussionsupporting
confidence: 89%
“…This is even though most bacteria are resistant against penicillins [36]. These findings are in agreement with what was found in studies that were done in Ethiopia, Cameroon, Nigeria, and Iraq [24,29,36,37]. These similarities in the findings could be due to the availability of these drugs in these various hospitals and hence their use.…”
Section: Discussionsupporting
confidence: 89%
“…Cameroon [33] have shown that laboratory testing reduces the odds of antibiotic prescribing. Our ndings showed that when laboratory investigations were requested prior to prescribing, patients were less likely to be prescribed with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Muchas de las prescripciones de antibióticos se realizan en forma empírica, superando en diversos estudios un 50% de los casos [17,18] . Adicionalmente, se debe considerar que cerca de una tercera parte a la mitad de las prescripciones de antibióticos son por infecciones del tracto respiratorio; y siendo la mayor parte de estas infecciones de origen viral, está demostrado que los antibióticos no afectan la duración, los síntomas y la intensidad de la enfermedad.…”
Section: Antibióticos En La Práctica Diariaunclassified